Utilization of banana peel for the removal of benzoic and salicylic acid from aqueous solutions and its potential reuse - Pathak, Pranav D.; Mandavgane, Sachin A.; Kulkarni, Bhaskar D. (Desalination and Water Treatment, 2016)
We report on the adsorptive removal of benzoic acid (BA) and salicylic acid (SA) using banana peel (BP), an abundantly available agricultural waste material, for the first time. BP was characterized by proximate analysis, FT-IR, scanning electron microscopy, BET surface area, and XRF. The number of basic sites on BP (4.9mmolg(-1)) is relatively more than acidic sites (0.75mmolg(-1)). The Langmuir uptake capacity values obtained are 6.62mgg(-1) for BA and 9.80mgg(-1) for SA. A mechanism for binding acid molecule to the BP surface is proposed.
Keywords: Adsorption; Banana peel; Benzoic acids; Salicylic acid; Wastewater treatment